(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2020)
Origin of parent materials and genesis of soils in the northwestern edge of the Bajos Submeridionales Basin, Santiago Del Estero, Argentina The Bajos Submeridionales basin comprises an extensive hydrological system in the eastern Chaco region of Argentina, which occupies the northern part of Santa Fe, the southern part of Chaco and eastern part of Santiago del Estero (Fig. 1). It is a large plain characterized by its low slope and the presence of fluvial, lacustrine and eolian sediments. Different source areas for the sediments have been proposed, as well as geomorphological processes controlled by regional climatic and tectonic dynamics. The aim of this study was to evaluate the influence of these processes in the genesis and distribution of parent materials and soils in the northwestern edge of the Bajos Submeridionales basin. For this purpose micromorphological studies in soil thin-sections, mineralogical analyzes by X-ray diffractometry (XRD) in bulk samples and in the clay-fraction samples, magnetic susceptibility (MS) measurements and soil physical and chemical analyzes (texture, organic matter, cation exchange capacity (CEC) and soil moisture equivalent) were performed. Four soil profiles developed in different landscape positions were studied: 1) Entic Haplustoll (C-50) in the gently undulating plain unit; 2) Typic Argiustoll (C-16) in the slope unit; 3) Typic Haplustert (C-53) in the low plane unit; and 4) Typic Endoacuert (C-27) in the drainage network (Fig. 2 and Table 1). Unlike the loess of Chaco region (Urundel Formation), microscopic studies show a high proportion of fresh acid volcanic glass in the coarser fractions. This composition relates it to the loess of Tezanos Pinto Formation, which covers the central and southern sector of the Bajos Submeridionales basin. Granulometric analyses show that the A horizon of the Haplustoll, Argiustoll and Haplustert soils have a finer texture than the subsurface B and C horizons. This could be related to the presence of lithological discontinuities in the parent materials. Effectively, both the high values of the estimated CEC for the clay-fraction and the soil moisture equivalent suggest an underestimation of the clay percentage in the granulometric analysis of the subsurface horizons (Table 2). In turn, micromorphological studies showed the presence of pseudo-sands and pseudo-silts and a high proportion of larger microaggregates of reworked soil material (i.e. Fig. 3b, Fig. 4c-d, Fig. 5b-c and Fig. 6b) in the subsurface horizons, in addition to inherited pedofeatures such as fragmented and deformed clay coatings (Fig. 3c-d). These features suggest that the soils parent material is constituted by sediments that has been eroded from pre-existing soils and transported to its current position. In turn, the angular- and subangular-blocky structure observed at the base of the Haplustoll (Fig. 4a) and the Haplustert (Fig. 6c) profiles, seems to constitute in situ soil relicts. The set of these characteristics of inherited microstructure and pedofeatures indicate the presence of a pedosedimentary paleosurface at the base of these profiles. For all profiles, the magnetic susceptibility values show two main sections separated by the paleosurface (Fig. 10). These first magnitude differences in the MS values are related to the characteristics and composition of the parent material. In Section I, the highest values ??are related to the volcaniclastic minerals of the regional loessic sediments and to the pedosedimentary components. This Section I is subdivided into three parts (Sub-section Ia, Ib and Ic) according to smaller magnitude variations, which are can be related to pedogenetic processes. In turn, the magnetic signal in Section II shows sharp and progressive decreases towards the base of the profiles. This variation in depth could be explained both by the increase in calcium carbonate and by the presence of sediments from local supply areas, such as the sandstones and the alluvial deposits of the Salado River. The XRD diagrams show the presence of illite, kaolinite and irregular interstratified of illite-smectite minerals (I-S) (Fig. 9). These minerals are found in different proportions along the profiles. The superficial A-horizons of the Haplustoll, Haplustert and Endoacuert show a dominance of illite, which can be related to the regional loessic sediments. Meanwhile, the pedosedimentary materials show a higher proportion of I-S minerals with smectite dominance. This be would related to both previous pedogenetic processes as well as the process of enrichment in smectites by transformation in the present soil, favored by the slightly alkaline chemical environment in the middle and basal sections of the profiles. The origin of the pedosediment could be linked to the erosion of a paleosurface, given by the tectonic dynamics and the climatic changes occurred during the Pleistocene. On the other hand, the mineralogical composition of the superficial A-horizons suggests that they could derive from the aeolian accumulation of sediments eroded by wind from the river channels, during an arid Holocene event. Then, the pedogenesis of these deposits would have occurred in a more humid recent event. These interpretations allow linking the pedological processes with the tectonic, sedimentary and climatic recent Quaternary cycles that occurred in this sector of the Bajos Submeridionales basin.